2003
DOI: 10.1046/j.1351-0754.2003.0561.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ectomycorrhizas on the concentration and biodegradation of simple organic acids in a forest soil

Abstract: Summary Simple organic acids seem to be important in many soil processes including nutrient uptake in the rhizosphere and long‐term pedogenic processes such as podzolization. The factors regulating the concentrations of these acids in soil, however, remain poorly understood. We have investigated one set of factors, namely the impact of ectomycorrhizal (Paxillus involutus) and non‐mycorrhizal Picea abies seedlings and humic acid on the concentration and dynamics of organic acids in soil solution. We did so over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 34 publications
(60 reference statements)
2
25
2
Order By: Relevance
“…A possible explanation for this discrepancy is uptake and transport of Al and Fe from the E horizon towards the O horizon by tree roots and EcM hyphae that exploit the E horizon but colonise root tips in the O horizon (see below on occurrence of EcM root tips and hyphae). Data by Griffiths et al (1994) for Hysterangium crassum and Gautieria monticola and by Van Hees et al (2003) for Paxillus involutus also indicated enhanced dissolution and mobilization of Al and Fe by EcM fungi. Possibly, siderophores exuded by EcM hyphae could play a role here because siderophores are even more efficient complexing agents than LMWOA (Haselwandter and Winkelmann 2002;Holmström et al 2004).…”
Section: Role Of Rock-eating Ecm Fungi In Aluminium Toxicity and Alummentioning
confidence: 90%
See 1 more Smart Citation
“…A possible explanation for this discrepancy is uptake and transport of Al and Fe from the E horizon towards the O horizon by tree roots and EcM hyphae that exploit the E horizon but colonise root tips in the O horizon (see below on occurrence of EcM root tips and hyphae). Data by Griffiths et al (1994) for Hysterangium crassum and Gautieria monticola and by Van Hees et al (2003) for Paxillus involutus also indicated enhanced dissolution and mobilization of Al and Fe by EcM fungi. Possibly, siderophores exuded by EcM hyphae could play a role here because siderophores are even more efficient complexing agents than LMWOA (Haselwandter and Winkelmann 2002;Holmström et al 2004).…”
Section: Role Of Rock-eating Ecm Fungi In Aluminium Toxicity and Alummentioning
confidence: 90%
“…Paxillus involutus produced several organic acids (Van Hees et al 2003;Yamaji et al 2005;Van Schöll et al 2006a), enhanced the weathering of muscovite (Van Schöll et al 2006b) and hyphae actively foraged for Mg (Van Schöll 2006). Some strains of this species (complex) showed high tolerance towards Al (Rudawska and Leski 1998) and one of two strains tested by could transport Al (Table 1).…”
Section: Weathering By Rock-eating Ecm Fungi -A Further Element Of Ecmentioning
confidence: 99%
“…Exudation of organic acids occurs close to the growing hyphal tips, but may also occur to some extent along hyphal lengths behind this zone (Sun et al 1999;van Hees et al 2006). Although several reports indicate that organic acid production by ECM (and indeed) nonmycorrhizal fungi is not a response to P limitation (Arvieu et al 2003;van Hees et al 2003;Rosling et al 2007), other studies suggest otherwise. Soluble oxalate production by Piloderma fallax increased with P deficiency in axenic culture (Tuason and Arocena 2009), while Paxillus involutus produced more malonate, but not oxalate, under P limitation in axenic culture, but did not do so during symbiotic growth with Pinus sylvestris (van Schöll et al 2006).…”
Section: Solubilisation Of Inorganic Phosphates By Ecm Fungimentioning
confidence: 93%
“…In all cases, concentrations of organic acids (butyric, propionic, acetic) were generally low and the mean values were higher in the rhizosphere of birch than of spruce. Yet, as noted by Van Hees et al (2003) for oxalate, the flux of LMMOAs through the soil is probably much faster than is suggested by the measurement of instantaneous concentration values. For crop plants such as durum wheat (Triticum turgidum var.…”
Section: Gradients Of Organic Substancesmentioning
confidence: 97%